Short communication: Emergence of novel A/G recombinant HIV-1 strains in Argentina - Fernández, María Florencia (2015)
The predominant circulating HIV-1 strains in South America are subtype B and B/F recombinants with different distributions among countries. However, the emergence of other subtypes is a matter of concern and needs continuous monitoring. We identified three different A/G recombinants in Argentina, two of them in vertically infected children from unlinked mothers and one in an adult female. HIV-1 pol sequences from the children showed novel A/G recombination patterns and no phylogenetic relationship with previously reported South American A/G sequences. The third A/G recombinant was a CRF06-cpx with African origin. The detection of new or unusual subtypes is important to avoid false-negative PCR HIV-1 early diagnosis due to detection failures and for future vaccine development.